2017
DOI: 10.1308/rcsann.2017.0025
|View full text |Cite
|
Sign up to set email alerts
|

Second generation cephalosporin antibiotic prophylaxis and Clostridium difficile infection in hip and knee arthroplasty

Abstract: Introduction The use of broad spectrum cephalosporin antibiotics has been discouraged by the Department of Health in England because of the link to increased Clostridium difficile infection rates. The aim of this study was to evaluate whether a local protocol that included the use of second generation cephalosporin (cefuroxime) antibiotics as a prophylactic agent was associated with increased risk of C difficile in elective hip and knee arthroplasty patients. Methods A retrospective intention-to-treat study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…[26] However, previous studies have suggested mixed results after CDAD and 2GC antimicrobial prophylaxis. [24,25,27] In the present study, the CDAD rate was similar between the short-term period and long-term period. Although changing the prophylactic antibiotics to a 2GC did not affect the incidence of CDAD, our result (4.9% of RC with IONB patients) is relatively high compared to those reported in other countries.…”
Section: Discussionsupporting
confidence: 67%
“…[26] However, previous studies have suggested mixed results after CDAD and 2GC antimicrobial prophylaxis. [24,25,27] In the present study, the CDAD rate was similar between the short-term period and long-term period. Although changing the prophylactic antibiotics to a 2GC did not affect the incidence of CDAD, our result (4.9% of RC with IONB patients) is relatively high compared to those reported in other countries.…”
Section: Discussionsupporting
confidence: 67%
“…The incidence of C. Difficile has been found to between 0 and 1.7% after THA and TKA surgery [ 1 ]. Antibiotics are used to prevent deep joint infection after surgery [ 25 ], and meta-analyses have found broad spectrum antibiotics, especially cephalosporins and clindamycin, to increase the risk of C. difficile infection 2-3-fold [ 26 ]. The increased risk of contracting C. difficile remains for up to 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of contracting C. difficile remains for up to 90 days. However, in a study by Al-Tawil et al the use of 3 peri- and postoperative doses of cefuroxime did not appear to be associated with an increase in C. difficile rates [ 26 ]. In this study, it was not possible to specify which antibiotics were used during the 7-year period in the 9 included high-volume centers since each region followed individual guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…However, this aspect seems specific to 3rd generation cephalosporins. Some studies have mentioned how 1st and 2nd generations cephalosporin regimens in surgical processes do not seem to show increased incidence or risk of C. difficile infections [42,43], which would allow its use as a reasonable alternative in enteral conversion, mainly when alternative options are limited by resistance or AE [44], as long as they are not used in the management of prostate infections where they have a poor diffusion [45].…”
Section: Discussionmentioning
confidence: 99%